2000
DOI: 10.1097/00007890-200002150-00012
|View full text |Cite
|
Sign up to set email alerts
|

Conversion to Mycophenolate Mofetil in Conjunction With Stepwise Withdrawal of Cyclosporine in Stable Renal Transplant Recipients1

Abstract: The stepwise switch from CsA to MMF was safe and mostly successful, and had beneficial effects on blood pressure, glomerular hemodynamics, and lipid profile. Beneficial trends were already present after partial withdrawal of CsA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
44
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 65 publications
3
44
1
Order By: Relevance
“…A possible contributing factor to the increased incidence of biopsy-proven rejections in our study might be the rapid CsA withdrawal. Although no significant difference was observed in our study between patients with two different withdrawalschedules, lower rejection rates have been described with a longer period of stepwise CsA withdrawal (18,23). Despite the higher incidence of acute rejections after discontinuation of CsA, no detrimental effect on creatinine clearance was noted.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…A possible contributing factor to the increased incidence of biopsy-proven rejections in our study might be the rapid CsA withdrawal. Although no significant difference was observed in our study between patients with two different withdrawalschedules, lower rejection rates have been described with a longer period of stepwise CsA withdrawal (18,23). Despite the higher incidence of acute rejections after discontinuation of CsA, no detrimental effect on creatinine clearance was noted.…”
Section: Discussioncontrasting
confidence: 72%
“…As a consequence of the intention-to-treat analysis, the effects of discontinuation of CsA are obscured by the proportion of patients in whom this drug was reintroduced (29%). In conversion studies with patients switching from CsA to azathioprine or MMF, beneficial effects on BP and lipid profile were also noted (18,26,29).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…8,9 There are limited data regarding whether different immunosuppressive regimens after heart transplantation may have a significant impact on progression of CAV. 10 It has been shown that the calcineurin inhibitors cyclosporine A (CsA) and tacrolimus (FK506), which cannot prevent CAV, 5,11 can induce endothelial dysfunction and hypertension, 12,13 which has been explained by an increase in vascular reactive oxygen species (ROS) formation. 14, 15 In contrast to this, the inhibitor of inosine monophosphate dehydrogenase (IMPDH), mycophenolate mofetil, or its active metabolite, mycophenolate acid (MPA), have been associated with positive effects on atherosclerosis or hypertension in animal models.…”
mentioning
confidence: 99%
“…Initially, several authors reported their retrospective experience of the conversion from CsA to MMF in patients who developed CsA nephrotoxicity, showing a significant improvement of renal function without AR after CsA withdrawal (5)(6)(7). In stable renal transplant recipients, CsA withdrawal under MMF was also found to be a safe procedure on the basis of the risk of AR and renal function (8,9), although histologic deterioration was observed in 50% of patients (10). Finally, the incidence of AR after CsA discontinuation under MMF was evaluated in three randomized trials (11)(12)(13).…”
mentioning
confidence: 99%